Sociological analysis of the palm oil in the Haut-Uele province, in DR Congo - SHINDANO, Jean-Claude; KABUITA, Leonard MUANASAKA; TONONDJO, Albert ONOTAMBA (IJRDO-Journal of Applied Science, 2021)
The palm oil is one of the most consumed oleaginous plants in the world used for a long time by local communities in Haut-Uele Province. The present investigation has tried to reveal the different uses that palm oil can do apart from its usual use, i.e., that of consumption by households. A sample of 130 individuals selected from 13 tribes in six territories that compose the Haut-Uele province. After the critical analysis, the results revealed that the palm oil is traditionally used in that region as remedy to 19 diseases, and in 11 customary ceremonies. However, other products of palm tree are also used at least in 18 practices. It has been proved that different uses of palm oil and the under products of the palm tree differ from one tribe to another, and between forest and savannah areas.